MARITIME INSECURITY IN THE GULF OF GUINEA: LESSONS LEARNT FROM THE STRUGGLE AGAINST SOMALI PIRACY - IBÁÑEZ GÓMEZ, FERNANDO (Journal of the Spanish Institute for Strategic Studies, 2018)
The objective of this article is to analyse what were the principal contributory factors in bringing about the almost total disappearance of Somali piracy in the last two years and to discover the lessons we have learnt so as to ascertain whether these can be applied in the struggle against piracy in the Gulf of Guinea. In doing so, we shall study the four elements considered critical: the greater effectiveness of an international military presence, the role of protection measures (in particular, the boarding of armed security personnel), the changes in Somalia’s domestic situation and the implementation of programmes put in place by various multilateral organisations designed to strengthen the capacities of the countries in the region. The conclusion reached is that some of the measures could be applied in the Gulf of Guinea but only with considerable difficulty, one example being the possibility of international military deployment or carrying private security teams on board. Nevertheless, in areas such as regional cooperation, strengthening the capacity of countries in the region or improving governance, much remains to be done in order to bring about a more secure maritime environment